Pengaruh Metode Permainan Adaptasi Congklak Terhadap Kemampuan Mengenal Angka Pada Anak Kelompok A di TK AL-IKHLAS - Sry Anita Rachman; Farlina Hardianti (Peneliti.net, 2021)
This study aims to determine the effect of the Congklak adaptation game method on the ability to recognize numbers in group A children at TK AL-IKHLAS Montong Agung. This research is quasi-experimental research, with a pre-test and post-test control group design. The populations of this study were all children in group A of TK AL-IKHLAS Montong Agung and the samples were groups A1 and A2 as control and experimental classes. Data collection techniques in this study used interviews, instrument validation and observation, while the data analysis technique in this study used the T-test using the SPSS 16.0 application. Based on the results of data analysis, it can be concluded that the congklak adaptation method has an influence on children's ability to recognize numbers in group A in the experimental and control groups, after being given treatment with a percentage of 76.7%, while the control group with 58.3%. The results of the T-test showed 0.000 <0.05 so it can be concluded that the congklak adaptation method has an influence on the children's ability to recognize numbers in group A.